2015
DOI: 10.3389/fnhum.2015.00369
|View full text |Cite
|
Sign up to set email alerts
|

Crossmodal deficit in dyslexic children: practice affects the neural timing of letter-speech sound integration

Abstract: A failure to build solid letter-speech sound associations may contribute to reading impairments in developmental dyslexia. Whether this reduced neural integration of letters and speech sounds changes over time within individual children and how this relates to behavioral gains in reading skills remains unknown. In this research, we examined changes in event-related potential (ERP) measures of letter-speech sound integration over a 6-month period during which 9-year-old dyslexic readers (n = 17) followed a trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 84 publications
(193 reference statements)
3
29
1
Order By: Relevance
“…The results indicated faster improvements at word reading and spelling measures in dyslexic children who followed the training in comparison to a control group of dyslexic children without training. Comparable findings were reported by Žaric et al (2015) who further showed that deficiencies in audiovisual ERP (MMN and a late negativity) modulations that are typically shown in dyslexic readers when being presented with letter-speech sound stimuli, are reduced by letter-speech sound training. Future research might therefore investigate whether dyslexics develop orthographically induced recalibration after longer periods of training to letter-speech sound combinations.…”
Section: Discussionsupporting
confidence: 75%
“…The results indicated faster improvements at word reading and spelling measures in dyslexic children who followed the training in comparison to a control group of dyslexic children without training. Comparable findings were reported by Žaric et al (2015) who further showed that deficiencies in audiovisual ERP (MMN and a late negativity) modulations that are typically shown in dyslexic readers when being presented with letter-speech sound stimuli, are reduced by letter-speech sound training. Future research might therefore investigate whether dyslexics develop orthographically induced recalibration after longer periods of training to letter-speech sound combinations.…”
Section: Discussionsupporting
confidence: 75%
“…Given that this print sensitivity develops with grapheme-phoneme correspondence learning in prereading children [Brem et al, 2010], it is likely that hampered letter-speech sound integration in dyslexic children affects the development of print sensitivity. A later negative electrophysiological response in audiovisual tasks between 300 and 700 ms is typically seen only in children [Froyen et al, 2008] and represents a later step in audiovisual integration, which is deficient in dyslexic children [ Zarić et al, 2015]. These electrophysiological findings provide evidence for deficient visual processing and audiovisual integration in dyslexia supporting hitherto existing knowledge from magnetic resonance imaging (MRI) studies.…”
Section: Introductionsupporting
confidence: 74%
“…Incongruency of the trained audiovisual information triggered a significantly weaker late electrophysiological response over posterior regions than untrained audiovisual stimuli. In previous studies, a late ERP around 600–750 ms showed differential processing for unexpected deviant as compared to standard crossmodal stimulation in children [Froyen et al, ; Moll et al, ; Žarić et al, ]. This differential late frontocentral negativity was enhanced for deviant (incongruent) stimuli expressing the impact of letters on speech sound processing and thus implying a delayed integration of grapheme‐phoneme pairs in beginning as compared to experienced adult readers [Froyen et al, ].…”
Section: Discussionmentioning
confidence: 86%
“…Beyond paired-associate learning-reflecting early acquisition processes-visualphonological associations remain impaired in dyslexia, even for highly-overlearned pairings, such as letter-to-letter sound associations (Blau, Van Atteveldt, Ekkebus, Goebel, & Blomert, 2009;Jones, Kuipers, & Thierry, 2016;Žarić et al, 2015). Failure to learn efficiently during the first exposures must therefore have long-term consequences for memory consolidation, despite potentially ameliorating factors such as practice and maturation (Snowling, 2000).…”
Section: Learning Mechanismsmentioning
confidence: 99%